The Effect of Microwave Baking Conditions on the Quality of Biscuits and the Control of Thermal Processing Hazards in the Maillard Reaction - Dong, Lu; Qiu, Caiyi; Wei, Fan; Yu, Zhenting; Zhang, Yan; Wang, Shuo (Frontiers in Nutrition, 2022)
To reduce thermal processing hazards (TPHs), microwave baking has been extensively used in food thermal processing. In this study, the influence of microwave power and microwave time on the formation of TPHs and their precursors was explored in microwave-baked biscuits. The results indicated that the content of acrylamide, 5-hydroxymethylfurfural, methylglyoxal, and 3-deoxyglucosone increased linearly with the extension of microwave time (2, 2.5, and 3 min) and microwave power (440, 480, and 520 W). There was a significant correlation between the four TPHs. 3-Deoxyglucosone may directly or indirectly participate in the formation of the other three TPHs. The relationship between TPH levels with some heat-induced sensory characteristics was analyzed. The correlation between the sensory characteristics and the content of TPHs is L* > a* > hardness > Water activity (AW). The correlation coefficients between L* value and the four TPHs are −0.950, −0.891, −0.803, and −0.985. Furthermore, the content of TPHs produced by traditional baking and microwave baking under the same texture level was compared. Compared with traditional baking (190°C, 7 min), microwave baking at 440 W for 3 min successfully decrease methylglyoxal, 3-Deoxyglucosone, acrylamide, and 5-hydroxymethylfurfural content by 60.75, 30.19, 30.87, and 61.28%, respectively. Traditionally baked biscuits, which had a more obvious color, as characterized by lower L* value, larger a* and b* values, are more susceptible to the formation of TPHs. Therefore, microwave baking can reduce the generation of TPHs.